Micro‐Blooming: Hierarchically Porous Nitrogen‐Doped Carbon Flowers Derived from Metal‐Organic Mesocrystals. Issue 37 (2nd July 2019) - Hwang, Jongkook; Walczak, Ralf; Oschatz, Martin; Tarakina, Nadezda V.; Schmidt, Bernhard V. K. J.
Abstract: Synthesis of 3D flower‐like zinc‐nitrilotriacetic acid (ZnNTA) mesocrystals and their conformal transformation to hierarchically porous N‐doped carbon superstructures is reported. During the solvothermal reaction, 2D nanosheet primary building blocks undergo oriented attachment and mesoscale assembly forming stacked layers. The secondary nucleation and growth preferentially occurs at the edges and defects of the layers, leading to formation of 3D flower‐like mesocrystals comprised of interconnected 2D micropetals. By simply varying the pyrolysis temperature (550–1000 °C) and the removal method of in the situ‐generated Zn species, nonporous parent mesocrystals are transformed to hierarchically porous carbon flowers with controllable surface area (970–1605 m 2 g −1 ), nitrogen content (3.4–14.1 at%), pore volume (0.95–2.19 cm 3 g −1 ), as well as pore diameter and structures. The carbon flowers prepared at 550 °C show high CO2 /N2 selectivity due to the high nitrogen content and the large fraction of (ultra)micropores, which can greatly increase the CO2 affinity. The results show that the physicochemical properties of carbons are highly dependent on the thermal transformation and associated pore formation process, rather than directly inherited from parent precursors. The present strategy demonstrates metal‐organic mesocrystals as a facile and versatile means toward 3D hierarchical carbon superstructures that are attractive for a number of potential applications. Abstract : Metal‐organic mesocrystals with 3D flower‐like superstructures are solvothermally synthesized and employed as versatile precursors for hierarchically porous nitrogen‐doped carbon with flower‐like appearance that is difficult to access through conventional synthesis methods. The control over pyrolysis temperature and associated in situ generation of porogens leads to high nitrogen content and (ultra)micropores, which increase the CO2 /N2 selectivity significantly.